2007
DOI: 10.1097/01.prs.0000244860.00674.57
|View full text |Cite
|
Sign up to set email alerts
|

Management of Vasospastic Disorders with Botulinum Toxin A

Abstract: Hand injection of botulinum toxin A appears to be an effective treatment for intractable digital ulcerations and rest pain in patients with severe vasospastic disorders. Because of the complexity of surgical digital artery sympathectomy along with its associated high risk of persistent symptoms, the authors conclude that the therapeutic use of botulinum toxin A injections represents an attractive alternative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 18 publications
5
129
0
3
Order By: Relevance
“…Although BoNTs are potential weapons for bioterrorism (Arnon et al, 2001), they are increasingly used for treating neurological and cardiovascular diseases, as well as for cosmetic purposes (Schnider et al, 1994;Benedetto, 1999;Tsuboi et al, 2002;Scott, 2004;Bilici et al, 2007;Van Beek et al, 2007;Schulte-Mattler, 2008). These uses provide a potential danger of intoxication with BoNTs.…”
mentioning
confidence: 99%
“…Although BoNTs are potential weapons for bioterrorism (Arnon et al, 2001), they are increasingly used for treating neurological and cardiovascular diseases, as well as for cosmetic purposes (Schnider et al, 1994;Benedetto, 1999;Tsuboi et al, 2002;Scott, 2004;Bilici et al, 2007;Van Beek et al, 2007;Schulte-Mattler, 2008). These uses provide a potential danger of intoxication with BoNTs.…”
mentioning
confidence: 99%
“…All but 5 patients experienced improved vascularity and relief of pain Neumeister et al (2009) 19 pts 84% reported pain reduction at rest and improvement of the perfusion and ulcerations Fregene et al (2009) 26 pts Statistically significant improvements were noted for pain score and digit transcutaneous oxygen saturation Van Beek et al (2007) 11 patients All patients reported highly significant pain reduction and 9 pts with ulcers spontaneously healed Kossintseva (2008) One patient The BT-A treated hand had reduced swelling, color change, and pain, whereas the untreated control hand remained affected Jenkins (2013) 10 pts randomized controlled study…”
Section: Studymentioning
confidence: 92%
“…In addition, 9 of 11 patients reported digital ulcer healing and 9 of 11 reported decreased severity and frequency of vasospastic episodes. 151 …”
Section: Botulinum Toxin-amentioning
confidence: 97%